2009
DOI: 10.1177/0961203308094996
|View full text |Cite
|
Sign up to set email alerts
|

Noonan syndrome associated with systemic lupus erythematosus

Abstract: Noonan syndrome (NS) is a developmental disorder characterised mainly by cardiac defects and craniofacial dysmorphia. An association between NS and some autoimmune diseases, such as thyroiditis and systemic lupus erythematosus (SLE), has been suggested. We report the case of a 28-year-old man with a diagnosis of NS and autoimmune hypothyroidism who developed symptoms and immunologic features of SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…They also showed partially similar presentations (e.g., age and the presence of serositis). A retrospective review of patients with SLE and a RASopathy phenotype revealed at least six patients with no accompanying genetic information (Alanay, Balc, & Ozen, ; Amoroso et al, ; Cerpa‐Cruz et al, ; Lisbona, Moreno, Orellana, Gratacos, & Larrosa, ; Lopez‐Rangel et al, ; Martin, Gencyuz, & Petty, ). It would be helpful to re‐evaluate these previous patients to determine whether they indeed have pathogenic variants in RASopathy genes, including SHOC2 .…”
Section: Discussionmentioning
confidence: 99%
“…They also showed partially similar presentations (e.g., age and the presence of serositis). A retrospective review of patients with SLE and a RASopathy phenotype revealed at least six patients with no accompanying genetic information (Alanay, Balc, & Ozen, ; Amoroso et al, ; Cerpa‐Cruz et al, ; Lisbona, Moreno, Orellana, Gratacos, & Larrosa, ; Lopez‐Rangel et al, ; Martin, Gencyuz, & Petty, ). It would be helpful to re‐evaluate these previous patients to determine whether they indeed have pathogenic variants in RASopathy genes, including SHOC2 .…”
Section: Discussionmentioning
confidence: 99%
“…Shared cardinal characteristics of the RASopathies include short stature, craniofacial malformations, webbed neck, cardiac malformation, variable cognitive delay and an increased risk of cancer development [80,81]. Twelve patients with NS/Noonan-related syndrome phenotype and SLE characteristics have been described to date [80][81][82][83][84][85][86][87][88][89][90][91]. Of these 12 patients, four had SHOC2 mutations, two had KRAS and one had a PTPN11 mutation [80,81,[84][85][86]90,91].…”
Section: Rasopathiesmentioning
confidence: 99%
“…Of these 12 patients, four had SHOC2 mutations, two had KRAS and one had a PTPN11 mutation [80,81,[84][85][86]90,91]. The remaining five patients with RASopathy and SLE are molecularly undiagnosed [82,83,[87][88][89]. Overall, the most frequently reported manifestation associated with SLE was arthritis (n = 8/11), followed by pericarditis/pleuritis (n = 7/11), autoimmune cytopenia (6/11), and skin involvement (n = 2/8).…”
Section: Rasopathiesmentioning
confidence: 99%
“…SHP2 is a ubiquitously expressed protein tyrosine phosphatase that modulates nearly all cytokine, integrin, and tyrosine receptor signaling pathways. It also appears to have a causal genetic link to SLE and other autoimmune-like disorders; indeed, more than 50 patients with NS, an autosomal dominant disorder principally caused by GOF SHP2 mutations, have been subsequently diagnosed with SLE (30)(31)(32)(33)(34)(35). Additionally, NS mice (SHP2 D61G/+ ) develop splenomegaly, have increased neutrophils and leukocytes, and develop an autoimmune-like disease (26).…”
Section: Figure 5 Shp2 Activity Specifically Modulates Dn T Cell Promentioning
confidence: 99%
“…Nearly all NS mutations of SHP2 are catalytically hyperactivated, i.e., they have increased PTP activity (23,24) and behave as gain-of-function (GOF) alleles (23)(24)(25)(26)(27)(28)(29). Importantly, to date, over 50 cases of NS have been linked to the development of SLE, as demonstrated by the onset of polyarthritis, pericarditis, and production of antinuclear and anti-DNA antibodies in these patients (30)(31)(32)(33)(34)(35). Taken together, these data suggest that a functional and/or genetic association between SLE and SHP2 activity likely exists.…”
Section: Introductionmentioning
confidence: 99%